2021
DOI: 10.14730/aaps.2021.00206
|View full text |Cite
|
Sign up to set email alerts
|

Remote migration of breast filler to the inguinal area: a case report

Abstract: Polyacrylamide hydrogel (PAAG) is an injectable material for breast augmentation that was developed in the 1980s. It was widely used until the 2000s, but subsequently lost its popularity due to high complication rates. In this case report, we share our experience of a patient complaining of hard and asymmetric breasts who had received PAAG injections 7 years ago. Surprisingly, we found that the filler in the left breast had migrated to the left inguinal area. Although breast fillers have lost ground in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
4
1
Order By: Relevance
“…One patient (case 1) showed invasive ductal carcinoma, but the relationship with the filler injection is unclear. Common complications reported in other studies, such as migration, masses, and infection, were not found in our cases, and studies also vary in terms of the interval until symptom onset, which was 13.2 years in our study, but less than 10 years in others [3,5,7,8].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…One patient (case 1) showed invasive ductal carcinoma, but the relationship with the filler injection is unclear. Common complications reported in other studies, such as migration, masses, and infection, were not found in our cases, and studies also vary in terms of the interval until symptom onset, which was 13.2 years in our study, but less than 10 years in others [3,5,7,8].…”
Section: Discussioncontrasting
confidence: 48%
“…It was banned in China in 2006; however, more than 30 million women have received PAAG injections for breast augmentation. Many patients with PAAG injections present with complications, such as inflammation, infection, lumps, deformities, a foreign body sensation, systemic toxicity, and immune system changes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Although injection is easy and has long-term clinical effects, many cases of complications such as infection and toxicity due to penetration into the surrounding tissue have been reported. [14,15,16] In our case, the injected filler was unknown. However, the injection of AQUAfilling was the most suspicious because many complications of AQUAfilling have been reported recently and the patient underwent the procedure in Korea.…”
Section: Discussionmentioning
confidence: 75%
“…[5] Although injection is easy and has long-term clinical effects, many cases of complications such as infection and toxicity due to penetration into the surrounding tissue have been reported. [14,15,16]…”
Section: Discussionmentioning
confidence: 99%
“…Unlike silicone implants, subcutaneously injected fillers have no barrier to contain the shape and stop migration. 1 There are case reports of filler material migrating to the inguinal area, 2 axilla, chest wall, abdominal wall, and peritoneum. 3 There has been one reported case of early migration of breast filler to the mediastinum—the material used as a breast filler was liquid silicone oil, and was discovered in the mediastinum 10 days after injection into bilateral breasts.…”
Section: Discussionmentioning
confidence: 99%